Anatomical Comparison of Radiofrequency Ablation Techniques for Sacroiliac Joint Pain. Issue 10 (5th February 2018) - Roberts, Shannon L; Stout, Alison; Loh, Eldon Y; Swain, Nathan; Dreyfuss, Paul; Agur, Anne M
Abstract: Objective: To compare the percentage of sacral lateral branches (LBs) that would be captured if lesions were created by seven current sacroiliac joint (SIJ) radiofrequency ablation (RFA) techniques: three monopolar and four bipolar. Design: Cadaveric fluoroscopy study. Setting: Anatomy and surgical skills laboratories. Subjects: Forty cadaveric SIJs. Methods: LBs were exposed, radiopaque wires were sutured to LBs, and anterior-posterior fluoroscopic images through the S1 superior endplate were obtained. Lesions that would be created by 17 versions of seven current SIJ RFA techniques were mapped on the fluoroscopic images. These 17 versions were compared: 1) percentage of LBs that would be captured; 2) percentage of SIJ specimens in which 100% of LBs would be captured; and 3) percentage of LBs that would not be captured at each level (S1–S4). Results: Both the mean LB and 100% capture rates were greater for the bipolar techniques (93.4–99.7% and 62.5–97.5%, respectively) than for the monopolar techniques (49.6–99.1% and 2.5–92.5%, respectively) evaluated. For the bipolar techniques, 1.5–29.2% of LBs would not be captured at S1 and 0% at S2-S4 vs 0–29.2% at S1-S4 for the cooled monopolar techniques vs 36.9–100% at S1-S4 for the conventional monopolar technique. Conclusions: The findings suggest that, if lesions were created, the RFA needle placement locations of the bipolar techniques evaluated may be capable of capturing all LBs, but those of the current monopolar techniques evaluated may not. Future in vivo imaging studies are required to compare the lesion morphology generated by different SIJ RFA techniques and correlate the findings with clinical outcomes.